Phylogenetic information of freshwater copepod (Diaptomus sicilis) with special reference to 18S rRNA - Mookkaiah, Gomathi Jeyam; Ravichandran, Ramanibai (International Journal of Biological Research, 2016)
In the present investigation to isolate freshwater calanoid copepods (Diaptomus sicilis) was characterized and identify the organisms by 18S rRNA sequencing. Plankton samples containing D. sicilis were collected during January 2014 (Post-monsoon) from Madippakkam Lake (12Â°57'41"N80Â°11'27"E) Chennai, Tamil Nadu. Immediately after sampling, specimens for genetic analyses were fixed in 95% ethyl alcohol. The total DNA was extracted from the individual copepod D. sicilis using Qiagen Blood tissue kit. The nuclear small subunit 18S rRNA gene was amplified using the Universal primer LCO â€”1490 (5â€™-GGTCAACAAATCATAAAGATATTGG-3â€™) and HCO-2198 (5â€™-TAAACTTCAGGGTGACCAAAAAATCA-3â€™). PCR products were loaded onto a 1% TAE agarose gel. Sequences were carried out an automated sequencer. The nucleotide sequence of 1282 base pair region of 18S rRNA was determined for D. sicilis. The similarity of sequences of D. sicilis was retrieved by BLASTn proÂgram and maximum identity and E-value was 76% and 0.00, respectively. The PCR products of D. sicilis individuals showed 80% similarity with the partial nuclear small subunit 18S rRNA gene region of other calanoid copepods. Based on molecular data the freshwater Calanoid copepods showed different algorithms and similar types of topologies useful for designing molecular analyses using phylogeny tree construction.Present molecular studÂies on the relationship of D. sicilis with other freshwater calanoid copepods indicate that this species is close to D. castor followed by D. keniraensis.